464 A Novel High Dose Rate Brachytherapy Device for Preventing Local Recurrence of Pancreatic Cancer Dosimetry Verification. (April 2022) - Verma, Rohan; Detels, Kelsey; Hoopes, Mary; Mohseni, Niam; Shumyeko, Dema; Yazdi, Youseph
Abstract : OBJECTIVES/GOALS: To demonstrate safety and limit damage to off-target organs, we will be determining dosimetry parameters through experimentation and Monte Carlo simulations with our brachy therapy applicator designed to improve upon current designs to treat a 3-dimensional volume. METHODS/STUDY POPULATION: Low-cost materials were used to manufacture our High Dose Rate (HDR) applicator and a readily available after loading system was used to load our configuration with a radioactive source. The dosimetry of our device was analyzed using commercially available software and external beam therapy films to generate depth dose profiles and superficial dose distribution. Additionally, we attempt to confirm Task Group No. 43 (TG-43) dosimetry parameters using Monte Carlo simulations for our device. These data were compared with currently available applicators used for intraoperative radiotherapy. RESULTS/ANTICIPATED RESULTS: We anticipate that we will be able to validate dosimetry parameters for our device in preparation for clinical use. We aim to show our dose distributions align well with proposed target volumes while considering the composition and shape of our applicator. We hope to demonstrate that, unlike current applicators, our design is more effective at treating a 3-dimensional target volume. DISCUSSION/SIGNIFICANCE: By 2040, pancreatic cancer will be the second-largest cause of cancer-related deaths. Even with current brachytherapy applicators, 30-40% of pancreatic cancer seems to recur near the surgical site after surgery. By preventing local recurrence, we hope to improve patient outcomes.